Effect of microcellulose modification methods on the properties of polypropylene composites - Quan Yuan; Guimei Zhang; Chunxuan Li; Liping He; Shiwei Xu (APL Materials)
Bio-based microcellulose/polymer composites are widely used in automotive interiors for their lightweight, environmentally friendly, and recyclable advantages, but their applications are limited due to the difficulty of dispersion in the matrix and their flammability. In this paper, we proposed the integrated functional modification of microcellulose with compatibility and flame retardancy, and then modified polypropylene composites with high strength, high thermal stability, and high flame retardancy were successfully prepared by extrusion–injection molding. Fourier infrared spectroscopy and x-ray diffraction analyses showed that the doping of Si/P/N synergistically modified microcellulose triggered a heterogeneous nucleation effect. Tests based on thermo-gravimetric analysis and differential scanning calorimetry showed that the polypropylene/synergistic modification of microcellulose by amino-silicone oil-phosphoric acid-melamine (PP/APMMCF) composites had the highest thermal stability and crystallinity; the compatibility between the modified microcellulose and PP matrix was improved as observed by scanning electron microscopy. Cone calorimeter and oxygen index meter analyses showed that PP/APMMCF could reduce the fire hazard.